Preliminary study of adaptation and validation of the Tolerance to Infidelity Scale - Vaqueiro Domingues, Andreia Filipa (2017)
Background & Aims: In Portugal, we did not find studies and instruments that evaluate tolerance to infidelity for the Portuguese population. Therefore, the aim of this preliminary study was to adapt and validate the Tolerance for Infidelity Scale (TIS) for the Portuguese population and to explore the associations between the tolerance for infidelity and different sociodemographic, relational, and regarding infidelity (and its forgiveness) variables, self-criticism and self-compassion. Methods: 223 individuals (women, 69.5%), with ages between 18 and 67 years old, answered a protocol consisting of a questionnaire with sociodemographic, relational and infidelity questions, the TIS, the Self-compassion Scale and the Forms of Self-criticizing/Attacking and Self-Reassuring Scale. Results: The adapted version for the Portuguese population of the TIS showed two dimensions: tolerance for sexual infidelity and tolerance for emotional infidelity. Both dimensions revealed good internal consistency: respectively, Cronbach's α = 0.896; α = 0.878. The tolerance for sexual infidelity presented good temporal stability and the tolerance for emotional infidelity very good temporal stability. Gender differences were not found regarding these dimensions. Participants who were married or were in a civil union scored higher in tolerance for sexual infidelity, in contrast with participants that were single, widows, were separated and divorced. Participants who reported having forgiven a situation of infidelity presented higher tolerance for sexual infidelity than those who did not. Also, participants that expressed not having difficulty in forgiving, presented higher tolerance for both types of infidelity, in comparison to who expressed difficulty in forgiving. Conclusions: The adapted version of the Tolerance for Infidelity Scale showed good internal consistency (total and subscales) and good temporal stability. The associations with marital status and with variables about forgiveness regarding infidelity seem to point out to the validity of the scale, but more studies are needed that explore, namely, the scale construct validity.